2005
DOI: 10.1038/modpathol.3800345
|View full text |Cite
|
Sign up to set email alerts
|

Regional over-representations on chromosomes 1q, 3q and 7q in the progression of hepatitis B virus-related hepatocellular carcinoma

Abstract: Hepatocellular carcinoma is a highly malignant tumor that is prevalent in Southeast Asia and China, where hepatitis B viral infection is the main etiologic factor. Despite a high incidence of hepatocellular carcinoma developing in patients with viral hepatitis B-induced liver cirrhosis, the molecular events underlying the malignant liver progression remain largely unclear. In an effort to characterize the genetic abnormalities involved in the hepatitis B-related liver carcinogenesis, we performed genome-wide e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 34 publications
1
30
1
Order By: Relevance
“…Dual-color fluorescence in situ hybridization (FISH) analysis was performed according as previously described. 18 Human bacterial artificial chromosome CTB-141D22 that embodied the PFTK1 gene and a reference clone RP11-110A23 on chr1p31.3 that seldom displayed imbalances in HCC 7 were differentially labeled with biotin-dUTP and digoxigenin-dUTP, respectively. Hybridized signals onto fixed cells of direct harvests or short-term cultures of primary HCC were visualized with avidin-conjugated FITC (Sigma, St Louis, MO), and anti-digoxigenin conjugated TRITC antibodies (Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual-color fluorescence in situ hybridization (FISH) analysis was performed according as previously described. 18 Human bacterial artificial chromosome CTB-141D22 that embodied the PFTK1 gene and a reference clone RP11-110A23 on chr1p31.3 that seldom displayed imbalances in HCC 7 were differentially labeled with biotin-dUTP and digoxigenin-dUTP, respectively. Hybridized signals onto fixed cells of direct harvests or short-term cultures of primary HCC were visualized with avidin-conjugated FITC (Sigma, St Louis, MO), and anti-digoxigenin conjugated TRITC antibodies (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…7q21-q22, to be closely associated with the advanced metastatic tumors. 7 Gains on the proximal 7q11.2-q31 have also been associated with metastatic colorectal carcinoma 8 and with the increased tumor vascularizations of prostate cancers. 9 In sporadic Burkitt's lymphoma 10 and esophageal squamous cell carcinoma, 11 gains of 7q with the smallest overlapping region mapped to 7q21-q22 have also been correlated with advanced pathological staging and shorter patient survivals.…”
mentioning
confidence: 99%
“…These aberrations have been correlated with etiological factors such as viral (hepatitis B, hepatitis C) infections. [12][13][14] Clinical impact has been reported for losses of 8p and gain of 20q with respect to stage and prognosis. 15 On the basis of genomic alterations detected by aCGH, hepatocellular carcinoma and its benign counterpart, hepatocellular adenoma, could be differentiated.…”
mentioning
confidence: 99%
“…Our group has previously conducted largescale correlative analysis on the genomic data derived from early and advanced stages hepatocellular carcinoma tumors with an aim to define the genetic aberrations involved in disease progression. 4 A number of regional copy gains were indicated, among which chromosome 7q34-q36 gains were common in the advanced metastatic hepatocellular carcinoma. 4 Distal chromosome 7q gains have been suggested in association with biliary tract carcinoma progression, 5 and higher-stage non-small cell lung cancer with nodal involvement.…”
mentioning
confidence: 99%
“…4 A number of regional copy gains were indicated, among which chromosome 7q34-q36 gains were common in the advanced metastatic hepatocellular carcinoma. 4 Distal chromosome 7q gains have been suggested in association with biliary tract carcinoma progression, 5 and higher-stage non-small cell lung cancer with nodal involvement. 6 Previous studies have also demonstrated a positive association between prostate cancer progression and copy gains of distal chromosome 7q, 7 and the amplification of chromosome 7q31-q36 region in the progression of gliomas to grade III or IV.…”
mentioning
confidence: 99%